Investigation of glucocorticoid and dissociated glucocorticoid activity in hepatoma cell lines with specific reference to regulation of the corticosteroid binding globulin (CBG) proximal promoter' - Allie-Reid, Fatima (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2003.